Sir Lance A-Little - Inns, Christopher (London: Orchard, 2013)
"Young Sir Lance-a-Little has a dangerous quest to fulfill. He must face an evil wizard, save a damsel in distress, outwit a hungry ogre, win a jousting contest, and battle a terrible creature whose name rhymes with flagon"--Back cover. Suggested level: junior, primary
Keywords: Children's stories